2013
DOI: 10.7196/samj.7137
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile of severe traumatic brain injury admissions to Red Cross War Memorial Children’s Hospital, 2006 - 2011

Abstract: The identification of aetiological factors and the description of demographic profiles of children sustaining TBI constitutes a basis for preventative policy administration and intervention strategies in SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 23 publications
6
39
0
Order By: Relevance
“…Outcomes for TBI in children are by and large good. [9,[11][12][13][14][15] Mortality was associated with low GCS on admission and was confined to the MVA and PVA cohorts. However, this gives a false sense of the severity of TBI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Outcomes for TBI in children are by and large good. [9,[11][12][13][14][15] Mortality was associated with low GCS on admission and was confined to the MVA and PVA cohorts. However, this gives a false sense of the severity of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, globally it would appear that in contrast to other public health problems such as cardiac diseases and infectious diseases, TBI has not been subject to adequate investigation or surveillance. [11][12][13][14][15][16][17][18] SA, with its excessive trauma burden, is typical in this regard. There is no national trauma registry to track the epidemic in general and there are only a handful of local reports and audits which document the situation as it pertains to TBI in SA.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority involve pedestrians (PMVCs), and traumatic brain injury accounts for up to 80% of childhood trauma deaths. [6][7][8][9] In addition to the burden of motor vehicle-related injuries, studies from Nigeria and SA have shown that gunshot wounds (GSWs) in infants and children are a tragic emerging mechanism of injury. [8,10,11] Although the number of hospital admissions following GSWs in Cape Town decreased between 2000 and 2007, the vast majority of deaths occurred before treatment could be instituted and a steady increase in admissions was seen in the subsequent 3 years.…”
mentioning
confidence: 99%